Complete Basilar Artery Assessment by Transcranial Color-Coded Duplex Sonography Using the Combined Transforaminal and Transtemporal Approach - Pade, O.; Eggers, J.; Schreiber, S. J.; Valdueza, J. (Ultraschall in der Medizin - European Journal of Ultrasound, 2011)
Purpose: Visualization of the basilar artery (BA) by transcranial color-coded duplex sonography (TCCD) can be challenging. The detection of stenosis or occlusion of the BA often has to rely on indirect signs like a highly pulsatile flow in the vertebral arteries. In case of a distal BA occlusion, however, the flow of the VAs can even be normal. The aim of our TCCD study was to visualize a maximum length of the BA combining the customarily used transforaminal appraoch for the proximal part and the less well known transtemporal coronal approach for the distal BA segment. Materials and Methods: TCCD was performed in 60 subjects with a good temporal bone window. Detectable extracranial or intracranial pathology was previously excluded. The BA was insonated using the transforaminal and transtemporal insonation plane and the visible length was measured. In one subject MRA was performed to substantiate our findings. Results: The BA was visualized in all subjects via both approaches. The maximal detectable BA length via the transforaminal and transtemporal approach was 26 ± 8 mm and 18 ± 5 mm, respectively. Assuming a previously reported average anatomical total BA length of 33 ± 6 mm, we supposed complete vessel visualization in 44 subjects (73 %). Conclusion: The combined transforaminal and transtemporal insonation approach may permit total BA insonation, thus facilitating the evaluation of BA pathology.
Keywords: ultrasound power Doppler; vascular; blood vessels; anatomy